The fern genus Oreogrammitis (Grammitidoideae: Polypodiaceae) re-defined - Parris, Barbara S.; Sundue, Michael A. (Phytotaxa, 2020)
Thirty-six new combinations are provided in Oreogrammitis Copel. (Polypodiaceae: Polypodiopsida). The species have previously been included in Radiogrammitis Parris and Themelium (T.Moore) Parris. Lectotypes are chosen for Polypodium allocotum Alderw., P. ctenoideum Brause, P. flagelliforme Brause, P. loherianum Christ, P. subpinnatifidum Blume and P. yoderi var. denudatum Alderw.